Christianity and critical race theory: a faithful and constructive conversation - Romero, Robert Chao (Baker Academic, a division of Baker Publishing Group, 2023)
"Critical Race Theory (CRT) is often poorly understood and unfavorably characterized. This accessibly written book offers a critical yet sympathetic introduction to CRT, bringing it into conversation with Christian theology and ministry practice"--